A Psychological Analysis of John Nash in " A Beautiful Mind by Ron Howard - Yuliana, Tiarma Ika; Octavita, Rr. Astri Indriana; Ulfa, Rima Novia; Ghufron, Muhammad Ali (JEdu: Journal of English Education, 2024)
This study deals with the psychological aspect of main character in A Beautiful Mind movie by Ron Howard. The study focus to find the dominant symptom of schizophrenia experienced by the main character.The study used the qualitative method with descriptive analysis technique. The data are taken from the scenes and dialogues in A Beautiful Mind movie. The subject of the research is John Nash as the main Character of A Beautiful Mind movie and the object are the schizophrenic symptoms. After analyzing the psychological of main character in A Beautiful Mind movie the writers found 35 data of schizophrenic symptoms. Twenty four data or 68, 5% of the data shows the positive symptom of schizophrenia, these are shown by the hallucination, delusion, speech and behavior disorder John Nash experience. Eleven data or 31, 5% of the data shows the negative symptom of schizophrenia which are shown in John Nash interaction in social life and lack of enjoyment in life.